Structure, Conduct, Performance (SCP) Approach & Fairness Principle in Business Competition Law in The Era of Digital Platforms - Jusmadi, Rhido; Aru Armando (JUSTITIA JURNAL HUKUM, 2024)
The emergence of digital platforms has led to disruptions that affect not only technological and economic aspects, but also legal aspects, particularly business competition law. The discourse surrounding the development of digital platforms within the context of business competition has been influenced by two major schools of thought: the Chicago School, which adopts an effeiciency approach (also known as the consumer welfare approach) , and the Harvard School, which employs the structure, conduct, and performance (SCP) approach. This article aims to scrutinize the shortcomings of the efficiency approach advocated by the Chicago School in addressing the issues related to business competition in the digital platform market. Additionally, it seeks to demonstrate how the principle of fairness, based on the competitive process approach and market strcture, can serve as a more comprehensive analytical tool for evaluating the health of competition in the market. The results show that the efficiency approach is inadequate in addressing concerns of fairness in the digital market. Responding to the context, global business competition authorities have begun to promote a fairness approach to bolster SCP approach which serves as a moral underpinning for upholding the principles of healthy business competition in the digital platform era. This article applied normative legal research methods with a conceptual approach for analysis.